Hydration Heat and Shrinkage of the Support of High-performance Concrete-filled Steel Tubes - Huibin Sun; Xiao Zhang; Leisheng Zhou; Xing Shao (Chemical Engineering Transactions, 2018)
To strengthen the prevention of cracks in hydration heat engineering. On the basis of summarizing and analyzing the models for hydration heat of concrete, numerical methods are used to calculate the temperature change curve of the core concrete in cement hydration stage. The thermal performance parameters of steel tubes and concrete are the essential basic data, which serves as a basis for research. Sectional dimension largely influences the shrinkage distortion of the core concrete in the concrete-filled steel tubes, which increases as the dimensions of the cross-section expand.